Nanoparticle albumin-bound paclitaxel in a patient with locally advanced breast cancer and taxane-induced skin toxicity: a case report - Cirauqui, Beatriz Cirauqui (BioMed Central, 2014)
INTRODUCTION: Taxanes have demonstrated effectiveness in the treatment of breast cancer, the most common type of cancer in women. The toxicity profile of taxanes (including skin toxicities) induces dose adjustment, delay, or discontinuation, which prevents a sufficient dose intensity to achieve a response. Nanoparticle albumin-bound paclitaxel, a solvent-free form of paclitaxel, prevents toxicities and reduces the pharmacokinetic interferences between paclitaxel and other drugs. CASE PRESENTATION: We describe the case of a 55-year-old Caucasian woman with locally advanced breast cancer treated with neoadjuvant therapy who developed secondary skin toxicity due to delayed hypersensitivity to taxanes. She received Adriamycin® (doxorubicin), cyclophosphamide and docetaxel and developed toxicity that promoted treatment delay and a switch to weekly paclitaxel. After the third and fourth weeks of treatment, paclitaxel toxicities also induced treatment delay and paclitaxel was switched to nanoparticle albumin-bound paclitaxel. She completed the five planned nanoparticle albumin-bound paclitaxel cycles with acceptable tolerability (including persistent grade 2 neuropathy) and without dose delay or adjustments. Clinical response was achieved although pathological response was not good. CONCLUSIONS: Nanoparticle albumin-bound paclitaxel treatment is a good option for patients with breast cancer with taxanes-related skin toxicity. This drug allows the treatment to be completed with acceptable tolerance in our case.